NILAI MORAL DALAM NOVEL WONG WADON DINARSIH KARYA TAMSIR A.S - Sahri, Alfi; Hapsari, Pradnya Paramita; Tri Widiatmi; R. Adi Deswijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the decline in morality among the younger generation. The novel Wong Wadon Dinarsih by Tamsir A.S. contains many moral values that can be studied and applied in everyday life. This study aims to describe the structure and moral values in the novel Wong Wadon Dinarsih by Tamsir A.S. The method used in this study is a qualitative descriptive method with a literature study technique. The source of data for this study is the novel Wong Wadon Dinarsih by Tamsir A.S. The research data consists of quotations and sentences that contain the structure of the novel and moral values in the novel Wong Wadon Dinarsih by Tamsir A.S. The data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusion drawing. The results of this study are (1) the structure that builds the novel includes the plot, characters and characterization, setting, and point of view in the novel Wong Wadon Dinarsih by Tamsir A.S. (2) the moral values contained in the novel include humans with themselves, humans with other humans, and humans with God.